USING OF INNOVATIVE TECHNOLOGIES DURING THE LESSON - Daniyarova Nilufar Dustmurodovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
Teaching and learning foreign languages are complex and long-lasting process. Interaction between teacher and students, process of the lesson and having comprehension or learning and teaching consciously depend on teacher’s competence. To show all competence and ability during the lesson teachers need innovative technologies. This article describes about using modern innovative technologies during the lesson.